PENERAPAN PETA KONSEP DALAM PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X MIPA-2 PADA MATERI USAHA DAN ENERGI DI SMA NEGERI 1 INDRAJAYA - Cut Surianti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2021)
In learning activities at SMA Negeri 1 Indrajaya, students only accept facts that must be memorized and there is still a lack of student involvement because they are almost always taught using the lecture method. The purpose of this study was to determine the application of concept maps in learning to improve learning outcomes X MIPA-2 on business and energy materials at SMA Negeri 1 Indrajaya. Concept maps make physics subjects more interesting and enable students to identify and interpret physics concepts and principles clearly. This will make it easier for students to get to the concepts that are important in physics. This classroom action research was carried out in Class X MIPA-2 SMA Negeri 1 Indrajaya with the research subjects being 30 students in class X MIPA-2. Data collection techniques used are tests and observations. The test is used to collect data about students' mastery and understanding (cognitive aspects) in the Effort and Energy material through an objective test in the form of multiple choice questions. While the observation was carried out to determine student learning outcomes in the affective and psychomotor aspects of students. The results of the learning carried out in the two cycles showed that in Cycle I there were 16 students who completed or 53.33% with a class average of 68.83. While in the second cycle there were 29 students who completed or 96.66% with an average grade of 79.83. Thus the research was stopped in cycle II. Based on the results of the study, it can be concluded that the application of concept maps in learning with learning steps according to RPP can improve student learning outcomes, both cognitive, affective and psychomotor. Suggestions that can be given to Physics teachers related to this research are to combine concept maps with other learning models or methods so that students do not get bored.Keywords : Concept Map, Learning Outcomes, Improvement